Ca1−xAxMnO3 (A = Sr and Ba) perovskite based oxygen carriers for chemical looping with oxygen uncoupling (CLOU). (1st November 2015) - Galinsky, Nathan; Mishra, Amit; Zhang, Jia; Li, Fanxing
Highlights: Sr and Ba are doped into the CaMnO3 structure for enhanced phase stability and CLOU properties. Strontium dopant helps to prevent irreversible decomposition of the perovskite structure. Sr-doped oxygen carriers have CLOU capabilities at lower temperatures while being redox stable. Computational techniques, such as DFT, can potentially be used to guide oxygen carrier selection. Abstract: Operated under a cyclic redox mode with an oxygen carrier, the chemical looping with oxygen uncoupling (CLOU) process offers the potential to effectively combust solid fuels while capturing CO2 . Development of oxygen carriers capable of reversibly exchanging their active lattice oxygen (O 2− ) with gaseous oxygen (O2 ) under varying external oxygen partial pressure (PO2 ) is of key importance to CLOU process performance. This article investigates the effect of A-site dopants on CaMnO3 based oxygen carriers for CLOU. Both Sr and Ba are explored as potential dopants at various concentrations. Phase segregations are observed with the addition of Ba dopant even at relatively low concentrations (5% A-site doping). In contrast, stable solid solutions are formed with Sr dopant at a wide range of doping level. While CaMnO3 perovskite suffers from irreversible change into Ruddlesden–Popper (Ca2 MnO4 ) and spinel (CaMn2 O4 ) phases under cyclic redox conditions, Sr doping is found to effectively stabilize the perovskite structure. In - situ XRD studies indicate that the Sr doped CaMnO3 maintains a stable orthorhombic perovskite structure under an inert environment (tested up to 1200 °C). The same oxygen carrier sample exhibited high recyclability over 100 redox cycles at 850 °C. Besides being highly recyclable, Sr doped CaMnO3 is found to be capable of releasing its lattice oxygen at a temperature significantly lower than that for CaMnO3, rendering it a potentially effective oxygen carrier for solid fuel combustion and carbon dioxide capture.